A Randomized Trial of Ligustrazini Hydrochlorioi in the Treatment of Viral Encephalitis in Children - Jiao, Fuyong; Guo, Xiangyang; Lin, Jin; Cui, Wei; Li, Huirong (Journal of Nepal Paediatric Society, 2010)
Introduction: Chuanxiong is a herb used in traditional Chinese medicine for the Treatment of viral encephalitis. In animal studies it has shown to inhibit the synthesis and activity of Thromboxane (TXA2) and abate the imbalance between Thromboxane (TXA2) and Prostacyclin (PGI2). As a result, cerebral edema, ischemia and hypoxia could be improved. The aim of this study is to evaluate its effect in the treatment of viral encephalitis in children. Methodology: Ninety-nine patients with viral encephalitis were randomly divided into two groups. Ligustrazini Hydrochlorioi (LH) consisting of 51 cases (males 30, females 21; age 5 years and nine month ±8 years and 2month) was given LH 4mg/kg per day in 100- 300mls of 10% glucose and infused intravenously over a three to four hour period, for 7 days as a course of treatment. A control groups of 48 cases (males 31, females 17; age 5 years and three month ±4 years and three month) received the conventional treatment of Vitamin C(2.0-3.0g), Coenzyme A(100u) and Adenosine Triphosphate (ATP) (40mg) in 100-300 mls of 10% glucose infused intravenously daily for 7 days. Results: The total response rate in the LH group and the control group were 94.12% and 68.75% respectively (u=3.271 p<0.05). The average time to improvement was 4.29±1.41 days and 7.31±2.66 days respectively. No adverse effect was observed in both groups. Conclusion: We conclude that LH is an effective, safe and well tolerated treatment for children encephalitis. Key words: Cerebral Oedema; Encephalitis; Ligustrazini Hydrochlorioi DOI: 10.3126/jnps.v30i2.3451 J. Nepal Paediatr. Soc. May-August, 2010 Vol 30(2) 119-122